Association of cerebrovascular reactivity and Alzheimer pathologic markers with cognitive performance. (25th August 2020) - Sur, Sandeepa; Lin, Zixuan; Li, Yang; Yasar, Sevil; Rosenberg, Paul; Moghekar, Abhay; Hou, Xirui; Kalyani, Rita; Hazel, Kaisha; Pottanat, George; Xu, Cuimei; van Zijl, Peter; et al.
Abstract : Objective: To determine whether MRI-based cerebrovascular reactivity (CVR) can predict cognitive performance independently of Alzheimer pathologic markers, we studied the relationship between cognition, CVR, and CSF-derived β-amyloid42 (Aβ42 ) and tau in a group of elderly individuals with mixed Alzheimer and vascular cognitive impairment and dementia. Methods: This was a cross-sectional study of 72 participants 69 ± 8 years of age consisting of individuals with normal cognition (n = 28) and cognitive impairment (n = 44) (including 36 with mild cognitive impairment [MCI] and 8 with mild dementia). CVR was measured with hypercapnia-MRI. Whole-brain CVR (percent blood oxygen level–dependent per 1 mm Hg EtCO2 ) was used to estimate vasodilatory capacity. Montreal Cognitive Assessment (MoCA) scores, cognitive domains scores, and a global composite cognitive score were obtained. AD biomarkers included CSF assays of Aβ42 and tau. Results: Whole-brain CVR was lower in the impaired (mean ± SE, 0.132 ± 0.006%/mm Hg) compared to the normal (0.151 ± 0.007%/mm Hg) group (β = −0.02%/mm Hg; 95% confidence interval [CI] −0.038 to −0.001). After adjustment for CSF Aβ42 and tau, higher whole-brain CVR was associated with better performance on the MoCA (β = 29.64, 95% CI 9.94–49.34) and with a global composite cognitive score (β = 4.32, 95% CI 0.05–8.58). When the CVR marker was compared with the Fazekas score based on white matter hyperintensities and vascular risk-score in a single regression model predicting the MoCA score, only CVR revealed a significant effect (β = 28.09, 95% CI 6.14–50.04), while the other 2 measures were not significant. Conclusions: CVR was significantly associated with cognitive performance independently of AD pathology. Whole-brain CVR may be a useful biomarker for evaluating cognitive impairment related to vascular disease in older individuals. Classification of evidence: This study provides Class II evidence that CVR was significantly associated with cognitive performance independent of AD pathology.